Sistema de control interno y su incidencia en la operatividad de los procesos de la empresa Clínica Contigo del Riñón Quevedo. período 2016-2017. - Urrutia Triviño, Cristina Elizabeth (2018)
The present investigation whose title is: "SYSTEM OF INTERNAL CONTROL AND ITS INCIDENCE IN THE OPERATION OF THE PROCESSES OF THE CLINICAL COMPANY WITH THE KIDNEY QUEVEDO, PERIOD 2016-2017", has as objective to evaluate the system of internal control and its effect in the execution of its operations. Clinic Contigo the kidney is a company with professional experts who provide health services in Nephrology, committed to comply with national and international standards of quality, environmental protection, safety and health at work of people, enhancing the skills of its employees and continuously improving the processes whose purpose is to permanently satisfy the interested parties. Internal Control is a system of processes that include the control of human talent, safeguard of assets, confirmation of information, compliance with policies and regulations and monitoring of operations, in order to make appropriate decisions and provide efficiency, effectiveness and effectiveness in each activity. The objective of this research in the Clinic Contigo the kidney Quevedo is to know how to apply the controls, rules and policies in the different areas of the company and provide guidance so that deficiencies that prevent it from achieving the achievement of its business goals can be corrected, benefiting the performance of employees and the execution of their activities.